Cats and dogs: A mesopredator navigating risk and reward provisioned by an apex predator. Issue 2 (22nd February 2022) - Brunet, Mitchell J.; Monteith, Kevin L.; Huggler, Katey S.; Clapp, Justin G.; Thompson, Daniel J.; Burke, Patrick W.; Zornes, Mark; Lionberger, Patrick; Valdez, Miguel; Holbrook, Joseph D.
Abstract: Successfully perceiving risk and reward is fundamental to the fitness of an animal, and can be achieved through a variety of perception tactics. For example, mesopredators may "directly" perceive risk by visually observing apex predators, or may "indirectly" perceive risk by observing habitats used by predators. Direct assessments should more accurately characterize the arrangement of risk and reward; however, indirect assessments are used more frequently in studies concerning the response of GPS‐marked animals to spatiotemporally variable sources of risk and reward. We investigated the response of a mesopredator to the presence of risk and reward created by an apex predator, where risk and reward likely vary in relative perceptibility (i.e., degree of being perceptible). First, we tested whether coyotes ( Canis latrans ) use direct or indirect assessments to navigate the presence of mountain lions ( Puma concolor ; risk) and kills made by mountain lions (reward) in an area where coyotes were a common prey item for mountain lions. Second, we assessed the behavioral response of coyotes to direct encounters with mountain lions. Third, we evaluated spatiotemporal use of carrion by coyotes at kills made by mountain lions. Indirect assessments generally outperformed direct assessments when integrating analyses into a unified framework; nevertheless, our ability to detect direct perception in navigating to mountain lion kills was likely restricted by scale and sampling limitations (e.g., collar fix rates, unsampled kill sites). Rather than responding to the risk of direct encounters with mountain lions, coyotes facilitated encounters by increasing their movement rate, and engaged in risky behavior by scavenging at mountain lion kills. Coyotes appear to mitigate risk by using indirect perception to avoid mountain lions. Our predator–predator interactions and insights are nuanced and counter to the conventional predator–prey systems that have generated much of the predation risk literature. Abstract : Successfully perceiving risk and reward can be achieved through direct or indirect cues. First, we tested whether coyotes (Canis latrans) use direct or indirect assessments to navigate the presence of mountain lions (Puma concolor; risk) and kills made by mountain lions (reward) in an area where coyotes were a common prey item for mountain lions. Second, we assessed the behavioral response of coyotes to direct encounters with mountain lions. Third, we evaluated spatiotemporal use of carrion by coyotes at kills made by mountain lions.